2014
DOI: 10.1177/0020764014522776
|View full text |Cite
|
Sign up to set email alerts
|

Homeless and incarcerated: An epidemiological study from Canada

Abstract: Homeless individuals may be traumatized at an early age, put into foster care, rendered homeless, initiated into substance use and re-traumatized on repeated occasions in adult life, rendering them vulnerable to incarceration and mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 44 publications
(41 reference statements)
1
27
1
4
Order By: Relevance
“…It is known that among substance abusers, sexual abuse is a major issue with a high prevalence, [34,35]. Previous studies indicate that childhood trauma could influence the severity, prognosis and evolution of crack cocaine consumption [36]. Other studies emphasize this finding, showing that the negative quality of initial liaison with parental care may be associated with the onset of trauma-related disorders, such as substance abuse [37].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that among substance abusers, sexual abuse is a major issue with a high prevalence, [34,35]. Previous studies indicate that childhood trauma could influence the severity, prognosis and evolution of crack cocaine consumption [36]. Other studies emphasize this finding, showing that the negative quality of initial liaison with parental care may be associated with the onset of trauma-related disorders, such as substance abuse [37].…”
Section: Discussionmentioning
confidence: 99%
“…Homelessness poses an increased risk of incarceration and incarceration in turn precipitates homelessness by disrupting social networks and employment opportunities 11 . For example, Saddichha et al 12 found an unusually high prevalence of incarceration among the homeless (65%) in three cities from Canada, which is higher than the 50%-55% prevalence that has been reported in earlier study from similar populations 5 . Incarceration and homelessness share many factors and this intertwined relationship poses those with history of both conditions at the greatest risk of suffering from mental health issues and substance abuse 12 .…”
Section: Introductionmentioning
confidence: 69%
“…Įvairūs tyrimai (Firzpatrick, Myrstol 2011;Mahs 2005;Metraux, Culhane 2006;Saddichha et al 2014) rodo, kad benamiai ar nakvynės namų gyventojai ne tik susiduria su būsto ir darbo problemomis, bet yra ir viena iš itin dažnai kriminalizuojamų grupių. Skirtingų tyrimų duomenimis, nuo 40 iki 80 procentų benamių ir nakvynės namų gyventojų yra atlikę bausmes įkalinimo įtaigose (Gowan 2002).…”
Section: įVadasunclassified
“…Skirtingų tyrimų duomenimis, nuo 40 iki 80 procentų benamių ir nakvynės namų gyventojų yra atlikę bausmes įkalinimo įtaigose (Gowan 2002). Nors ir konstatuojama, kad benamystė ir įkalinimas yra itin glaudžiai susiję, tačiau akademinis susidomėjimas benamystės ir įkalinimo sankirtų analize išlieka itin menkas (Gowan 2002;Metraux, Culhane 2006;Saddichha et al 2014).…”
Section: įVadasunclassified
See 1 more Smart Citation